Integrating Green and Inclusive Practices for Financial Performance: Evidence from Indonesia Listed Consumer Firms (2019-2023) - Elvetta Zada Ardiana; Majidah Majidah (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Financial performance is the work achievement attained by a company within a specific period. Companies that consistently generate profits are companies with good financial performance. However, the financial performance of companies in the primary consumer goods sector in 2019-2023 fluctuated, as seen from the average Return on Capital Employed. Therefore, this study aims to analyze factors that can improve financial performance, including using Green Accounting, Quality Management System, Gender Diversity, and Circular Economy. The object of this study is primary consumer goods companies listed on the IDX in 2019-2023. Using purposive sampling, a sample of 52 companies or 260 observation data was obtained. The research data was analyzed using panel data regression. The results showed that only gender diversity had a negative effect on financial performance.